Laparoscopic Radical Nephrectomy: The New Gold Standard Surgical Treatment for Localized Renal Cell Carcinoma. (2007) - Eskicorapci, Saadettin Yilmaz; Teber, Dogu; Schulze, Michael; Ates, Mutlu; Stock, Christian; Rassweiler, Jens J.
Abstract : We will try to demonstrate that laparoscopic radical nephrectomy could be the new gold standard treatment for renal cell carcinoma with the aid of the current reports exploring the advantages and disadvantages of laparoscopic radical nephrectom overopen surgery. Reported perioperative outcomes like operating time, blood loss, postoperative analgesia requirement, and length of hospital stay and duration of convalescence had been found to be in favor of laparoscopic radical nephrectomy. Some technical issues like approach of laparoscopic technique (Transperitoneal versus retroperitoneal laparoscopic nephrectomy), removal of dissected specimen and need for lymph node dissection had been also discussed in detail in this review. Besides, oncological safety of laparoscopic radical nephrectomy had been explored. The overall five-year disease free survival rates of laparoscopic radical nephrectomy in recent series were found to be over 90%. All of the series including the present one at least confirmed the oncological efficacy of LRN as compared with open surgical approach. The contemporary review of the literature documents clearly demonstrated the perioperative benefits of laparoscopy compared to the open approach. Nevertheless, the development, however, more safe and reliable technique in laparoscopy is necessary for tumor extraction. Recent studies confirmed the long-term similar cancer control results of laparoscopic radical nephrectomy with open surgery. Despite some technical modifications by the different groups, it can be stated that laparoscopic radical nephrectomy is the new gold standard treatment modality for patients with localized renal cell carcinoma.